Nucleus-Satellite Analysis and Conjugation Mediation in Coptic and Later Egyptian - Grossmann, Eitan (Zeitschrift für ägyptische Sprache und Altertumskunde, 2008)
The syntactic analysis of the class of elements known as 'preverbal extensions,′ 'conjugation mediators′ or 'preverbals′ is known to be problematic, specifically with regard to nucleus-satellite analysis. In short, it is a matter of debate whether or not the conjugation mediator is to be analyzed as the head of its construction. In the first section of this article, the specific criteria for assessing nuclear status are made explicit, and it is suggested that the conjugation mediators cannot be analyzed as heads or satellites, as for the most part, they do not belong to the verb phrase as such and do not contract a relationship of dependence with the verbal lexeme itself. In the second section, a Demotic construction is analyzed as a pre-Coptic conjugation modifier, closest to Bohairic 'je′. In the third section, some Late Egyptian patterns involving pre-lexemic spatial adverbials are discussed in light of conjugation mediation. The Demotic and Late Egyptian evidence suggests that the phenomenon of conjugation mediation is not an innovation of Coptic, but rather existed as a structural option already in pre-Coptic Egyptian.